Answer: 4.5
Explanation:
First, find the points of intersection by solving the system.
y = x² + 2x + 4
y = x + 6
Solve by substitution:
x² + 2x + 4 = x + 6 ⇒ x² + x - 2 = 0 ⇒ (x + 2)(x - 1) = 0 ⇒ x = -2, x = 1
Now, integrate from x = -2 to x = 1
the bottom of the integral is -2
=
=
=
![(-x^(3))/(3) - (x^(2))/(2)+2x\int\limits^1_2 {} \,](https://img.qammunity.org/2019/formulas/mathematics/middle-school/gfbu746w3gw8kheq2dpipjhl2x55col1q7.png)
=
![((-1^(3))/(3) - (1^(2))/(2)+2(1)) - ((-(-2)^(3))/(3) - ((-2)^(2))/(2)+2(-2))](https://img.qammunity.org/2019/formulas/mathematics/middle-school/3uhbzoahevifm3k267w1xxqgc4g3nlo3fc.png)
=
![((-1)/(3) - (1)/(2) +2) - ((8)/(3) -(4)/(2) -4)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/2qo6n5y92xx9umcd64gx76leyhh7yd50yi.png)
=
![(-9)/(3) + (3)/(2) +6](https://img.qammunity.org/2019/formulas/mathematics/middle-school/gbsjrt7ob2cjnk0eojlz0tbv70e3i67bum.png)
= -3 + 1.5 + 6
= 4.5